Implementasi Program Kampus Mengajar 1 - Rifan Shodikin; Asep Dudi Suhardini (Bandung Conference Series: Islamic Education, 2022)
Abstract. The teaching campus is one of the derivative programs of the Independent Learning Independent Campus policy issued by the Ministry of Education and Culture. Participants of this program are students while the target of this program is Elementary School. Of course, students know that they must first know the MBKM policy. Various student backgrounds to be able to join this program. Then with the Campus Teaching program, it is certainly in line with the PAI study program, where the goal is to produce professional teachers in their fields. The type of approach used in this research is a qualitative approach with a case study method. The technique of collecting data is through interviews, and documentation studies. The result of this study is that students already know in advance about the MBKM policy, although not comprehensively. Then the motivation of students in participating in this program is first for personal self-development such as the development of soft skills and hard skills, as well as to seek experience and contribute to the development of the world of education. The relevance between the teaching campus program and the Islamic Religious Education study program is only on matters related to teaching and teacher training. Because the purpose of the Islamic education study program is to produce professional teachers in their fields. While in the implementation of the campus teaching the participants are required to be able to solve various problems that exist in the school. Abstrak. Kampus mengajar merupakan salah satu program turunan dari kebijakan Merdeka BelajarKampus Merdeka yang di keluarkan oleh Kementerian Pendidikan dan Kebudayaan. Peserta dari program ini merupakan mahasiswa adapun target dari program ini merupakan Sejolah Dasar. Tentunya mahasiswa mengetahui harus mengetahui terlebih dahulu terkait kebijakan MBKM. Beragam latar belakang mahasiswa untuk dapat mengikuti program ini. Kemudian dengan adanya program Kampus Mengajar ini tentunya selaras dengn program studi PAI yang mana tujuan nya ialah untuk mencetak guru professional dalam bidangnya. Jenis pendekatan yang digunakan pada penelitian ini adalah pendekatan kualitatif dengan metode studi kasus. Adapun teknik pengumpulan data melalui wawancara, dan studi dokumentasi. Hasil penelitian ini adalah mahasiswa sudah mengetahui terlebih dahulu terkait kebijakan MBKM walaupun tidak secara komperhensif. Kemudian motivasi mahasiswa dalam mengikuti program ini yang pertama ialah untuk pengembangan diri pribadi seperti halnya pengembangan soft skill dan hard skill, serta untuk mencari pengalaman dan turut berkontribusi dalam pengembangan dunia pendidikan. Adapun relevansi antara program kampus mengajar dengan program studi Pendidikan Agama Islam ialah hanya pada hal-hal yang terkait pengajaran dan keguruan. Karena tujuan program studi pendidikan Agama Islam ialah mencetak guru professional pada bidangnya. Sedangkan dalam pelaksanaan kampus mengajar para peserta dituntut untuk dapat menyelesaikan berbagai permasalahan yang ada di sekolah tersebut.